Field practice study of half‐dose sorafenib treatment on safety and efficacy for hepatocellular carcinoma: A propensity score analysis. Issue 3 (28th May 2014) - Morimoto, Manabu; Numata, Kazushi; Kondo, Masaaki; Kobayashi, Satoshi; Ohkawa, Shinichi; Hidaka, Hisashi; Nakazawa, Takahide; Okuwaki, Yusuke; Okuse, Chiaki; Matsunaga, Kotaro; Suzuki, Michihiro; Morita, Satoshi; et al.
<x xml:space="preserve">Abstract</x> Aim Patients with hepatocellular carcinoma (HCC) who receive an initial full dose of sorafenib (800 mg/day) often require a decreased dose (400 mg/day) or discontinuation of therapy because of severe adverse events. We conducted a retrospective analysis of patients with HCC to compare the safety and efficacy of full‐ to half‐dose sorafenib. Methods We reviewed the medical records of 218 consecutive patients with intermediate or advanced stage HCC who received half (n = 73) or full‐dose sorafenib (n = 145) between 2009 and 2012 at four institutions. A propensity score‐matching analysis was used to adjust for potential bias. Results Multivariate logistic regression analysis showed that increased age was an independent factor for the selection of initial half‐dose sorafenib (odds ratio, 1.10; 95% confidence interval, 1.05–1.15; P < 0.001). Fifty‐eight patients each in the half‐dose and full‐dose groups were selected for propensity score matching. The incidence of grade 3–4 severe adverse effects was lower in the half‐dose group (47.4% vs 66.7%, P = 0.037). In contrast, the median progression‐free survival (PFS) and overall survival (OS) rates were not significantly different (half‐dose group, 3.8 and 10.2 months; full‐dose group, 2.5 and 8.8 months; P = 0.143 and 0.911, respectively). Conclusion Propensity score‐matched analyses indicate that initial half‐dose sorafenib treatment led to fewer severe adverse effects and a comparable survival benefit compared with a full dose in select patients with HCC, particularly for those of advanced age.